2012
DOI: 10.1051/0004-6361/201219541
|View full text |Cite
|
Sign up to set email alerts
|

Supernovae and their host galaxies

Abstract: Context. In this first paper of a series, we report the creation of large and well-defined database that combines extensive new measurements and a literature search of 3876 supernovae (SNe) and their 3679 host galaxies located in the sky area covered by the Sloan Digital Sky Survey (SDSS) Data Release 8 (DR8). Aims. This database should be much larger than previous ones, and should contain a homogenous set of global parameters of SN hosts, including morphological classifications and measures of nuclear activit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 56 publications
(86 citation statements)
references
References 94 publications
2
82
0
1
Order By: Relevance
“…In this second paper of a series, using a well-defined and homogeneous sample of host galaxies from the SDSS, presented in the first paper (Hakobyan et al 2012), we analyse the number ratios of different SN types (NIa/NCC, N Ibc /NII, and NIc/N Ib ) in spirals with various morphologies and in barred or unbarred galaxies. We also explore the variations in the number ratios with different levels of morphological disturbance of the hosts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this second paper of a series, using a well-defined and homogeneous sample of host galaxies from the SDSS, presented in the first paper (Hakobyan et al 2012), we analyse the number ratios of different SN types (NIa/NCC, N Ibc /NII, and NIc/N Ib ) in spirals with various morphologies and in barred or unbarred galaxies. We also explore the variations in the number ratios with different levels of morphological disturbance of the hosts.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to take into account the fact that SNe Ia explode in all morphological types of galaxies, while CC SNe explode mostly in spiral and irregular hosts (e.g. van den Bergh, Li & Filippenko 2005;Hakobyan et al 2008Hakobyan et al , 2012. Therefore, to exclude SNe type biasing due to host-galaxy morphology, we further restrict the sample to SNe detected in spiral galaxies (including S0/a types).…”
Section: Sample Selectionmentioning
confidence: 99%
“…We do not show these measurements in Figure 10, but note that as they vary in the range ≈ 0.2-0.4, they would be broadly consistent with the other measurements in the plot. Hakobyan et al (2012Hakobyan et al ( , 2014 used a subsample of SNe from the Asiago Supernova Catalog (Barbon et al 1999) and the Sternberg Astronomical Institute (SAI) Supernova Catalog (Tsvetkov et al 2004) to measure N Ibc /N II in galaxies with different morphologies and disturbance levels (e.g., interacting vs. merging galaxies). They found that N Ibc /N II is lower in late-type (Sc-Sm) galaxies than in early-type (S0/a-Sbc) at a 5% significance level, which is consistent with the trend we observe.…”
Section: Sn Rates Vs Number Ratiosmentioning
confidence: 99%
“…SN 2007pk (Fig. 2), discovered in the Scd galaxy NGC 579 (Hakobyan et al 2012) on 2007 November 10.31 UT, has been classified as a young "peculiar" type IIn SN resembling SN 1998S at early phases (Parisky et al 2007). Immler et al (2007) reported a bright X-ray source within 23 .5 from the SN position although, due to the large point-spread-function of the XRT instrument (18 half-power diameter at 1.5 keV) the error box include the galaxy nucleus.…”
Section: Sne and Their Host Galaxiesmentioning
confidence: 99%
“…3. SN 2010aj was discovered in the Sc galaxy (Hakobyan et al 2012) MGC-01-32-035 by Newton et al (2010) on 2010 March 12.39 UT and was classified as a young type II SN resembling the type IIP SN 2006bp near maximum brightness (Cenko et al 2010). The recession velocity of MGC-01-32-035 corrected for the Virgo infall is v Virgo = 6386 ± 20km s −1 (Mould et al 2000, from NED), corresponding to a distance modulus µ = 34.71 ± 0.15 mag.…”
Section: Sn 2009dd (mentioning
confidence: 99%